Disaster Response Training; First Aid for Cardiac Arrest Patients by Involving Health Workers in The Disaster Task Force Team Public High School - Wasliyah, Siti; Fadillah, Lailatul; Rahmadi, Roby (POLTEKKES KEMENKES BANTEN, 2023)
Disaster events in Indonesia, both natural and non-natural disasters, are familiar to all Indonesian people. Tangerang City is one of the disaster-prone areas in Banten. State Senior High School 06 Tangerang City is one of the public schools located in Tangerang city where the location is located in a disaster-prone area. SMA Negeri 06 is a school that does not yet have a disaster task force but its students have already had PMI KSR extracurricular activities. The problem found in students is that there is still a lack of understanding about non-traumatic disaster victims, namely cardiac arrest and the lack of ability to provide first aid to cardiac arrest patients as a disaster mitigation effort. Students also do not understand about mapping disaster areas at school and evacuation routes at school. The results of this activity Most students know about cardiac arrest and CPR, and there is an increase in the average ability to perform CPR skills. Teachers and students played an active role in training the first handling of cardiac arrest patients. Suggestions recommended based on the results of this community service activity are that this activity can be carried out sustainably where the training material is continued on handling disaster victims according to the type of disaster. Another activity is that the active task force team in conducting training can collaborate with the Regional Disaster Management Agency (BPBD), the Indonesian Red Cross (PMI) and the Banten Polytechnic, Tangerang Nursing Department according to needs..